2013
DOI: 10.1039/c3ta11871a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the chemical activity through PtAu nanoalloying: a first principles study

Abstract: The electronic structure and adsorption properties of 1.5 nm sized Pt, Au, and PtAu nanoclusters are studied by density functional theory. We explain the recent experimental finding that 20% Au content in PtAu nanoparticles is optimal to induce a dramatically different catalytic behavior. Our results show that the d-band center together with the density of states at the Fermi energy can be used as an indicator of the chemical activity of PtAu nanoclusters. The most favorable adsorption sites on the cluster sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…43 As for the PtAu system, it has been theoretically predicted as well as experimentally proved that strong dissociative adsorption of hydrogen can take place more efficiently on Pt clusters than on Au clusters (or mixed PtAu sites). [16][17][18][19] In our case, from the synthesis point of view it is reasonable to propose the presence of a small number of clusters, which may be even under the detection limit, on the surface as a result of laser ablation. Clustered atoms have been reported to be present in the plasma plume formed by laser ablation.…”
Section: Fabrication Of Ptau-np/ceo 2 -Nt Hybrid Catalystsmentioning
confidence: 77%
See 1 more Smart Citation
“…43 As for the PtAu system, it has been theoretically predicted as well as experimentally proved that strong dissociative adsorption of hydrogen can take place more efficiently on Pt clusters than on Au clusters (or mixed PtAu sites). [16][17][18][19] In our case, from the synthesis point of view it is reasonable to propose the presence of a small number of clusters, which may be even under the detection limit, on the surface as a result of laser ablation. Clustered atoms have been reported to be present in the plasma plume formed by laser ablation.…”
Section: Fabrication Of Ptau-np/ceo 2 -Nt Hybrid Catalystsmentioning
confidence: 77%
“…Bimetallic nanostructures have recently attracted considerable attention due to their improved catalytic properties as compared to monometallic NPs for several catalytic reactions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] For example, Stamenkovic et al reported the enhancement in the kinetics of the oxygen-reduction reaction (ORR) using PtM (M ¼ Ni, Co, Fe) alloy NP catalysts in fuel cells, and revealed that the surface electronic structure of alloy NPs has an important effect on their electrocatalytic activity. 1,2 Elsewhere, Huang et al reported the enhanced catalytic activity of PtPd alloy nanocrystal catalysts for the hydrogenation of nitrobenzene and showed that the activity depends on the structure and composition of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…33 The adsorbed BH 4 − on Pt surface can be easily dissociate to activated [H] and then these resulting activated [H] can be facilely migrated to Au owing to their alloy structure, where the reduction reaction is taken place. 34 In the case of inert oxides (SiO 2 or ZrO 2 ), the electronic structure of Pt─Au is not changed by the oxides, thus the reaction process of 4-NP is proposed to be that the Pt NPs adsorb BH 4 − and dissociate it to activated [H]. Then these [H] can be easily transferred to Au surface and reacts with 4-NP.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous theoretical and experimental study on the bimetal Pt─Au nanocatalysts, it is well suggested that 4‐NP prefers to adsorb on Au, while BH 4 − is more likely to adsorb on Pt . The adsorbed BH 4 − on Pt surface can be easily dissociate to activated [H] and then these resulting activated [H] can be facilely migrated to Au owing to their alloy structure, where the reduction reaction is taken place . In the case of inert oxides (SiO 2 or ZrO 2 ), the electronic structure of Pt─Au is not changed by the oxides, thus the reaction process of 4‐NP is proposed to be that the Pt NPs adsorb BH 4 − and dissociate it to activated [H].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, tremendous attention has been paid to bimetallic nanostructures for several catalytic reactions due to their improved catalytic properties compared to monometallic NPs [18][19][20][21][22]. The surface electronic structure of hybrid NPs has an important effect on their electrocatalytic activity and has enhanced the kinetics of the oxygen-reduction reaction (ORR) in experiments using Pt-M (M¼Ni, Co, Fe)-hybrid NP catalysts in fuel cells [23,24].…”
Section: Introductionmentioning
confidence: 99%